Investigation into the relationship between cognitive abilities, academic performance and interdisciplinary project work - Tan, Ai Bee (2008)
The purposes of the study were to investigate two situations: if there were significant differences in a group of students' academic performance and Interdisciplinary Project Work (PW) assessment performance when they are classified into Ability Profile Groups; and if there were significant relationship between these students' individual scores obtained from the Morrisby General Abilities Tests (GAT, 1995) for Verbal, Numerical and Perceptual abilities with their academic performance and PW assessment performance.